Juridical Analysis of the Inclusion of Standard Clauses Regarding Changes in Investment Fund Management Fees Unilaterally by Business Actors in Life Insurance Policies PT Prudential Life Assurance - Devia Candrawati; Eny Sulistyowati (Universitas Negeri Surabaya, 2024)
This study explores the legal issues surrounding standard clauses in life insurance agreements, focusing on clause Number 5.6 in the policy of PT Prudential Life Assurance. Insurance serves as a form of risk management in response to life’s uncertainties. However, standard agreements, particularly in life insurance, often favor business actors and may disadvantage consumers. One such clause requires consumers to accept unilateral changes made by the insurer, raising concerns under consumer protection law. The research aims to analyze the normative conflict between Prudential’s policy clause and Article 18(1)(g) of the Consumer Protection Act and Article 22(3)(f) of Financial Services Authority Regulation No. 1/POJK.07/2013. The study also examines the legal remedies available to consumers who are affected by such clauses. Using a normative juridical method with statutory and conceptual approaches, the study relies on primary and secondary legal materials. The findings conclude that Clause 5.6 contradicts the aforementioned legal provisions, as it allows unilateral changes by the insurer, which is prohibited in consumer agreements. This violates principles of fairness and legal certainty. As a result, consumers may pursue legal remedies through both litigation (e.g., filing claims in court) and non-litigation avenues (e.g., dispute resolution bodies or mediation), in accordance with Indonesia’s positive law. The study highlights the need for stronger regulatory oversight and enforcement to protect consumer rights in the financial services sector.